ANALYSIS OF FACTORS RELATED TO NURSE RETENTION IN SOURCE LIVING HOSPITAL AMBON - Lambonaung, Ellen; Yusuf, Andi; Azis, Rahmawati (Jurnal Kesehatan, 2022)
Employee retention is the time interval from starting work until the end of the work period in a place. Many factors have an impact on the high level of nurse retention, including competitive salaries, a healthy work environment, productive leadership and clear career management. This study aims to determine how the retention of nurses at Sumber Hidup Hospital – Ambon. The research was conducted at Sumber Hidup Hospital, Ambon. This type of research is a quantitative research with an observational approach using a cross sectional design. Sampling on nurses was carried out randomly. Data collection uses primary data and secondary data. Data were analyzed using statistical analysis through cross tabulation followed by chi-square test, namely univariate and bivariate analysis. The results showed that there was a relationship between career paths (ρ=0.000 < 0.05), nurse salaries (ρ=0.007 < 0, 05), motivation (ρ = 0.007 < 0.05), reward (ρ = 0.000 < 0.05) with nurse retention at Sumber Hidup Hospital in Ambon. Suggestions for the Sumber Hidup Ambon Hospital to be able to carry out evaluations related to the management system that is applied in order to support and provide good motivation for nurses and this supports the retention of nurses in the hospital.